KULINTANG STATESIDE: ISSUES ON AUTHENTICITY OF TRANSFORMED MUSICAL TRADITIONS CONTEXTUALIZED WITHIN THE GLOBAL/LOCAL TRAFFIC - Onishi, Pamela Costes (Humanities Diliman: A Philippine Journal of Humanities, 2010)
A resurgence of interest in the Philippine gongs and drum tradition called kulintang took place in the United States from the late twentieth century. It is performed in its traditional style but has also seen several transformations. This study examines the popularity of the kulintang among Filipino American academics, artists, and the youth. It seeks to answer questions about the authenticity of traditions, as they are transported into an unfamiliar territory and given new forms of dynamism by individuals or groups for their own immediate needs to locate their identities. The concepts of authenticity and the traditional are becoming more and more slippery in this globalized age. When situated within the phenomena of transnational movements of people and swift exchanges between cultural practices, it becomes impossible to adhere to a fixed definition of what are authentic and traditional without essentializing the culture bearers or “ethnic artists.” This paper takes into account the present transnational and global conditions in answering the questions of “what is authentic” and “what is traditional” in music. It acknowledges the inevitability of redefining these concepts as personal needs change in historical and cultural contexts, and how individual choices for creativity and self-identification are limited and affected by transnational flows. The paper calls for a pluralistic view of the kulintang tradition, as it is bounded by the authenticity of its new bearers.
Keywords: Kulintang , Filipino-American Music, Transnationalism, Globalization, Authenticity, Tradition